Aboveground Whitefly Infestation-Mediated Reshaping of the Root Microbiota - Kong, Hyun G.; Kim, Byung K.; Song, Geun C.; Lee, Soohyun; Ryu, Choong-Min (Frontiers in Microbiology, 2016)
Plants respond to various types of herbivore and pathogen attack using well-developed defensive machinery designed for self-protection. The phloem-sucking insect infestation such as whitefly and aphid on plant leaves were previously shown to influence both the saprophytic and pathogenic bacterial community in the plant rhizosphere. However, the modulation of the root microbial community by plants following insect infestation has been largely unexplored. Only limited studies of culture-dependent bacterial diversity caused by whitefly and aphid have been conducted. In this study, to obtain a complete picture of the belowground microbiome community, we performed high-speed and high-throughput next-generation sequencing. We sampled the rhizosphere soils of pepper seedlings at 0, 1, and 2 weeks after whitefly infestation versus the water control. We amplified a partial 16S ribosomal RNA gene (V1–V3 region) by polymerase chain reaction with specific primers. Our analysis revealed that whitefly infestation reshaped the overall microbiota structure compared to that of the control rhizosphere, even after 1 week of infestation. Examination of the relative abundance distributions of microbes demonstrated that whitefly infestation shifted the proteobacterial groups at week 2. Intriguingly, the population of Pseudomonadales of the class Gammaproteobacteria significantly increased after 2 weeks of whitefly infestation and confirmed the recruitment of fluorescent Pseudomonas spp. exhibiting the insect-killing capacity. Additionally, three taxa, including Caulobacteraceae, Enterobacteriaceae, and Flavobacteriaceae, and three genera, including Achromobacter, Janthinobacterium, and Stenotrophomonas, were the most abundant bacterial groups in the whitefly-infested plant rhizosphere. Our results indicate that whitefly infestation leads plant recruiting specific group of rhizosphere bacteria conferring beneficial traits for host plant. This study provides a new framework for investigating how aboveground insect feeding modulates the belowground microbiome